KANDUNGAN ENERGI DAN BETA KAROTEN KULIT PISANG GOROHO (Musa Acuminafe. Sp) HASIL FERMENTASI - Pipinharyono Muda; Ellen J Saleh; Sri Suryaningsih Djunu; Syamsul Bahri (xxxx-xxxx, 2022)
This study aims to determine the gross energy and beta carotene content ofgoroho banana peel (Musa acuminafe. sp) fermentedas animal feed. This research was conducted in August - September 2021. The research site is at the Laboratory of Animal Nutrition, Department of Animal Husbandry, Faculty of Agriculture, State University of Gorontalo. The research method used is this research method using a completely randomized design (CRD). Parameters observed in this study were beta carotene content and gross energy in Goroho banana peel fermented using Rizhopus Oligosporus and Trichoderma Viride inoculum . These data were then analyzed by Duncan's further test .The results showed that Gross Energy P3 P0.05 was significantly different and Beta-carotene P0 P0.05. The results of this study can be concluded that Treatment 3 which is fermented goroho banana peel flour feed with an inoculum dose of Rhizopus Oligusphorus + Trichoderma Viride  0.3% and a fermentation time of 120 hours can increase the gross energy by 5469 kcal/kg and Treatment 0 which is banana peel flour goroho without fermentation with inoculum has a high beta-carotene content of 0.64 mg/100g.